Pengalaman Perempuan Dalam Asuhan Kebidanan Masa Kehamilan: Studi Kualitatif - Sri Wilujeng, Anik; Izzati, Dwi; Frety, Endyka Erye; Djuari, Lilik (Yayasan Jompa Research and Development, 2025)
A positive pregnancy experience is a condition in which the mother feels supported physically, emotionally, and socially. It is closely related to the model of midwifery care provided. The midwifery care model will influence the effectiveness of the services delivered. One of the recommended models of care is the Midwifery-Led Continuity Model of Care. The aim of this study is to analyze women’s experiences in receiving midwifery care during pregnancy. Methods: This was a qualitative study with a phenomenological design. The research subjects consisted of eight participants selected using a purposive sampling technique. Data were collected through in-depth interviews. Results: The pregnancy experience was perceived as pleasant, which was attributed to the care programs offered, including the incorporation of complementary care. Conclusion: All forms of care provided were essential and continuous, taking into account the physical, psychological, social, and cultural backgrounds of pregnant women. Through a comprehensive approach and appropriate empowerment, midwifery services are expected to foster better understanding, enhance satisfaction, and provide a positive and meaningful pregnancy experience for every woman.